The “Controversy Over Translations” Reflected in 19th-Century English-Chinese Dictionaries Compiled by Missionaries in China - WU Lijing, (Journal of Research for Christianity in China (JRCC), 2025)
Translating Bible and compiling bilingual dictionaries were the two important missions conducted by most of the Protestant missionaries as soon as they arrived in China in the early 19th century. In translating Bible, they soon dived into an irreconcilable controversy over the proper Chinese term to convey the meaning of God. Some preferred Shangdi while others were in favor of Shen, thus provoking the Term Question. Most of the missionaries involved in the controversy were confronted with a proper choice when compiling their English-Chinese dictionaries. This paper intends to trace their choice of Chinese terms as suitable counterparts for God, in order to reestablish the evolutional process of the semantic equivalence between God and Shangti on the one hand, and on the other hand to disclose the seemingly objective dictionary-compiling activity as an historical product which embodies the compiler’s intention. Dictionary plays an important role in shaping human thought. The spread of missionary dictionaries as well as Bible has eventually fostered a new meaning to Shangdi, which replaces its original meaning in a subtle way.